Asymmetric synthesis of a lignan lactone from a meso anhydride - Ward, Robert S.; Pelter, Andrew; Edwards, Mark I.; Gilmore, Jeremy (Tetrahedron, 1996)
The synthesis of a meso-2,3-dibenzylbutanedioic acid anhydride is given. Reaction of this with (+)-α-methylbenzylamine proceeds diastereoselectively to give a butanedioic acid monoamide which is converted into an enantiomerically enriched cis-2,3-dibenzylbutyrolactone lignan. Graphic